2015
DOI: 10.15171/joddd.2014.023
|View full text |Cite
|
Sign up to set email alerts
|

Social and Behavioral Determinants for Early Childhood Caries among Preschool Children in India

Abstract: Background and aims. Early Childhood Caries (ECC) is a public health problem with biological, social and behavioural determinants and the notion that the principal etiology is inappropriate feeding modalities is no longer tenable. Hence this study was undertaken to assess the relationship between ECC and socio-demographic factors, dietary habits, oral hygiene habits and parental characteristics.Materials and methods. The study involved a dental examination of 1400 children aged 0-71 months, recording caries us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
55
2
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 16 publications
13
55
2
25
Order By: Relevance
“…In both cases, there was an association between caries and the mother's educational level, nutritional status, child age, and presence of clinically visible plaque. The same associations were identified by others researches in different countries [12,14].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In both cases, there was an association between caries and the mother's educational level, nutritional status, child age, and presence of clinically visible plaque. The same associations were identified by others researches in different countries [12,14].…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have demonstrated the correlation between the frequency of sucrose intake at early ages and the prevalence of caries [12,22]. The influence of dietary habits has been particularly evident in the case of severe early childhood caries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations